CARBONATE REDUCTION BY FE-S-O MELTS AT HIGH PRESSURE AND HIGH TEMPERATURE - Gunn S.C.; Luth R.W. (My University, 2006)
Diamond may form in the Earth's mantle by recrystallization of graphite, by precipitation from a C-bearing fluid, or by reduction of carbonate. The latter mechanism could result from interaction with a reduced fluid or another phase that would accommodate the oxygen produced by the reduction. One possible such phase is a sulfide-bearing melt, given that sulfides are common inclusions in diamond. Experiments at 1300 °C, 6 and 7.5 GPa successfully reduced magnesite in the presence of a eutectic-composition Fe-S-O melt. Although graphite rather than diamond was produced by this reduction, these experiments demonstrate that this mechanism is a viable mechanism for reducing carbonate to carbon in the Earth's mantle.
Keywords: CRYSTAL SYNTHESIS; EXPERIMENTAL PETROLOGY; HIGH-PRESSURE STUDIES; IGNEOUS PETROLOGY